BILINGUAL EDUCATION FOR THE DEAF - Nascimento, Lilian Cristine Ribeiro (2022)
This article aims to present the different interpretations of bilingual education for the deaf in the state of São Paulo, which result in different education proposals for deaf people. For this, a qualitative research was carried out, starting from the analysis of the federal laws that govern the education of the deaf, comparing them with the state policy and also with the local policies of 4 municipalities in the state of São Paulo. In addition, field research was carried out in the school units, making it possible to verify whether the legal proposals were, in fact, implemented in school practices. The data collected in the school units refer to the year 2018. As a result, it was found that the policies implemented by the state and the analyzed municipalities, for the most part, do not fully contemplate the federal legislation, nor meet the demands of the deaf community